Diagnosing the canvas: challenging the diagnosis of Prader–Willi syndrome in Eugenia Martínez Vallejo (1674-1699) - Uri Hamiel; Orit Pinhas-Hamiel (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Eugenia Martínez Vallejo (1674-1699), famously portrayed by Juan Carreño de Miranda at the court of King Carlos II of Spain, has long been considered a historical example of Prader–Willi syndrome (PWS). More than 20 publications have supported this diagnosis based on her severe obesity, facial appearance, and presumed small extremities. We revisited this diagnosis using historical medical documentation, auxological analysis, and next-generation phenotyping. Historical documents preserved from that period describe hyperphagia beginning immediately after birth, with a weight of 25 kg at 1 year of age, inconsistent with the natural history of PWS, typically characterized in infancy by hypotonia and feeding difficulties. In addition, Eugenia’s estimated height at age 6 years, derived from the dimensions of a life-size portrait, corresponds approximately to the 95th percentile for age, arguing against the short stature characteristic of PWS. Given these inconsistencies, we considered alternative diagnoses within the leptin–melanocortin pathway disorders associated with severe early-onset obesity. Application of DeepGestalt facial phenotyping did not support PWS. Bardet–Biedl syndrome (BBS) was suggested with low-to-moderate confidence. However, the absence of historical evidence for key syndromic features, including polydactyly, neurodevelopmental impairment, and progressive vision loss, makes BBS unlikely. Eugenia’s accelerated linear growth and absence of overt syndromic or dysmorphic features are compatible with melanocortin receptor 4 deficiency, in which affected individuals typically present with isolated severe early-onset obesity. This case illustrates how integrating historical records, clinical reasoning, and AI-based phenotyping can challenge longstanding diagnostic assumptions and broaden the differential diagnosis of severe early-onset obesity.